Biological acellular pericardial mesh regulated tissue integration and remodeling in a rat model of breast prosthetic implantation. Issue 2 (15th May 2019) - Bernardini, Roberta; Varvaras, Dimitrios; D'Amico, Federico; Bielli, Alessandra; Scioli, Maria Giovanna; Coniglione, Filadelfo; Rossi, Piero; Buonomo, Oreste C.; Petrella, Giuseppe; Mattei, Maurizio; Orlandi, Augusto
Abstract: The use of biological meshes has proven beneficial in surgical restriction and periprosthetic capsular contracture following breast prosthetic‐reconstruction. Three different types (smooth, texturized, and polyurethane) of silicone round mini prostheses were implanted under rat skin with or without two different bovine acellular pericardial biological meshes (APMs, BioRipar, and Tutomesh). One hundred eighty‐six female rats were divided into 12 groups, sacrificed after 3, 6, and 24 weeks and tissue samples investigated by histology and immunohistochemistry. Implantation of both APMs, with or without prostheses, reduced capsular α‐SMA expression and CD3 + inflammatory cell infiltration, increasing capillary density and cell proliferation, with some differences. In particular, Tutomesh was associated with higher peri‐APM CD3 + inflammation, prosthetic capsular dermal α‐SMA expression and less CD31 + vessels and cell proliferation compared with BioRipar. None differences were observed in tissue integration and remodeling following the APM + prostheses implantation; the different prostheses did not influence tissue remodeling. The aim of our study was to investigate if/how the use of different APMs, with peculiar intrinsic characteristics, may influence tissue integration. The structure of APMs critically influenced tissue remodeling after implantation. Further studies are needed to develop new APMs able to optimize tissue integration and neoangiogenesis minimizing periprosthetic inflammation and fibrosis.